DAKWAH HUMANIS SEBAGAI UPAYA PENANGGULANGAN RADIKALISME DI INDONESIA - ARIFAH NURTSANIA ARDIYANTI (Fakultas Dakwah dan Komunikasi, 2018)
Nowadays, radicalism becomes a particular interest of Indonesian society. The emergence of acts of terror in different shapes and places ranging from religion places to government places. It raises many assumptions. Indonesia is a special country. Why? Because Indonesia is the country with the largest Muslim populations in the world. However, it will only bring the perception which has relation with radicalism. Indonesia, with the largest Muslim populations in the world can not be separated or otherwise become the victim of terrorist acts in whisch ‘the west’ regarded that the terrorists are Muslims. Basically, there are efforts such radicalism prevention efforts that can be done by Indonesia people in particular. As Muslims who ‘rahmatan lil alamin’ which merciful, full of love, and peace, in fact, in utself has an obligation to preach deliver enjoining good and forbidding wrong. This article will review one of the forms of religious proselytizing, namely the humanist religious proselytizing as a solution to overcoming radicalism.